AB1107 Epidemiological Comparative Analysis in a Large Cohort of Systemic Lupus Erithematosus Patients: Results of the Spanish IMID Consortium. (9th June 2015) - Fernández Nebro, A.; Carreira, P.; Blanco, R.; Pérez Venegas, J.; Olive, A.; Andreu, J.L.; Aguirre, A.; Vela, P.; Marenco, J.L.; Nolla, J.M.; Zea, A.; Pego, J.M.; et al.
Abstract : Background: Systemic Lupus Erithematosus (SLE) is a complex disease of unknown etiology, involving both genetic and environmental factors. Objectives: The aim of this study was to analyze the more relevant epidemiological characteristics in a large cohort of patients with SLE and controls in the Spanish population. Methods: A cross-sectional, comparative, multicenter study of patients with SLE and hypernormal healthy subjects for IMID diseases was performed. All patients were recruited through the Immune-Mediated Inflammatory Diseases Consortium (IMIDC).The IMIDC is a network of Spanish biomedical researchers focused in the study of the molecular basis of immune-mediated inflammatory diseases. All patients included in the present study were selected from the outpatient clinics of 13 Rheumatology Departments at different Spanish University Hospitals. An epidemiological questionnaire developed by experts at DNA National Bank was applied to obtain all data Results: 1, 070 SLE patients and 1, 558 healthy subjects were included. 93% of SLE patients and 40% of controls were female. The mean age of SLE patients and controls was 45±13 years and 49±7 years respectively. In the univariate analysis, we observed that the height and weight of the control subjects was significantly higher than in patients with SLE. The level of statistical significance was decreased by introducing gender and age as covariates. Both SLE patients (55%) and control subjects (68%) mostly had secondary or higher education. The physical exercise was significantly more frequent in controls. The gender and age affect the assessment of physical activity performed by both groups of patients. Regarding employment status, most patients with SLE (35%) were housewives whereas in the control group were external employers (44%). Both SLE patients (36%) and controls (52%) most frequently use their private cars. The average consumption of tobacco, alcohol was higher in the control group but the significance level decreased in multivariate analysis, confirming the influence of gender and age on these variables. We observed a statistically significant diference on the average consumption of coffee and frequency of smoking after adjusting by confounding factors. No statistically significant differences were observed in the average number of children when comparing both groups. Conclusions: In this large comparative study we describe for the first time the general epidemiological characteristics in patients with SLE and healthy subjects representative of the Spanish population. SLE patients are younger, have lower consumption of coffe/tea and smoke more often than healthy controls. The influence of gender confirms the significance level of variables such as physical activity, alcohol intake, weight and height. Disclosure of Interest: None declared